Factors Impacting Ethical Behavior in Hospitals - Deshpande, Satish P. (Journal of business ethics, 2006)
This study examines factors impacting ethical behavior of 203 hospital employees in Midwestern and Northwestern United States. Ethical behavior of peers had the most significant impact on ethical behavior. Ethical behavior of successful managers, professional education in ethics and sex of the respondents also significantly impacted ethical behavior. Nurses were significantly more ethical than other employees. Race of the respondent did not impact ethical behavior. Overclaiming scales indicated that social desirability bias did not significantly impact the results of our study. Implications of this study for researchers and practitioners are discussed.